The Effect of Social Media Marketing and Word of Mouth on Customer Loyalty in Moderation by Brand Image at Lenggang Monas Jakarta - Diansyah Diansyah; Golmer Horas Hutagaol (Budapest International Research and Critics University, 2022)
This research is about the influence of social media marketing and word of mouth on customer loyalty moderated by the brand at Lenggang Monas Jakarta. The total population is the traders who are in the Lenggang Monas Jakarta. The method in this research is a side-by-side by randomly distributing it. This research was conducted to find out how the influence between the variables studied is how the influence of social media marketing on customer loyalty, the influence of word of mouth on customer loyalty, brand image on customer loyalty and to find out whether brand image moderation is able to strengthen or weaken the influence of social media marketing. and to find out how brand image is able to strengthen or weaken the influence of word of mouth on customer loyalty. This research was carried out in several stages, namely the first taken from the bibliography, statistics and collecting the object being researched. Second, to test the feasibility of data and data collection. The third hypothesis testing using SEM PLS. The results of the study are social media marketing has an insignificant effect on customer loyalty, word of mouth has no significant effect on customer loyalty, brand image has a significant effect on customer loyalty, moderation of brand image can weaken the influence of social media marketing on customer loyalty, moderation of brand image can weaken the effect of word of mouth on customer loyalty.